2015
DOI: 10.47513/mmd.v7i3.406
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mothers’ Voice on the Long Term Development of Premature Infants: A Prospective Randomized Study

Abstract: Language acquisition appears to begin during fetal life. This is substantiated by the fact that the fetus recognizes and remembers the voice and melody of the mother's language. We hypothesized that Auditory Stimulation of preterm infants with their mothers' voice may also improve their language and overall development. 24 preterm infants were exposed on a daily basis 5 times for 30 minutes to the recorded voice of their mothers for 6 to 10 weeks beginning 1 to 3 weeks after birth. A control group of 24 infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…This result might not only reflect that preterm infants recognized the known music but also that they perceived it as more arousing and pleasant ( Lordier et al, 2018 ). Other studies have reported positive effects on behavioral development after exposure to a breathing bear ( Thoman et al, 1991 ; Ingersoll and Thoman, 1994 ), to the sound of a heartbeat ( Barnard and Bee, 1983 ), or to voices ( Nöcker-Ribaupierre et al, 2015 ; Filippa et al, 2017 ; Best et al, 2018 ; Saliba et al, 2018 ) during the NICU stay. However, the long-term effects of music listening in the NICUs on preterm infant’s cognitive and emotional development have never been explored so far.…”
Section: Introductionmentioning
confidence: 99%
“…This result might not only reflect that preterm infants recognized the known music but also that they perceived it as more arousing and pleasant ( Lordier et al, 2018 ). Other studies have reported positive effects on behavioral development after exposure to a breathing bear ( Thoman et al, 1991 ; Ingersoll and Thoman, 1994 ), to the sound of a heartbeat ( Barnard and Bee, 1983 ), or to voices ( Nöcker-Ribaupierre et al, 2015 ; Filippa et al, 2017 ; Best et al, 2018 ; Saliba et al, 2018 ) during the NICU stay. However, the long-term effects of music listening in the NICUs on preterm infant’s cognitive and emotional development have never been explored so far.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to recorded mother's voice is given to babies between 10:00 WIB (western Indonesia time) to 19:00 WIB (western Indonesia time), in 2 different shifts. The recording is played using a small speaker, placed in an incubator about 20 cm from the baby's ear with a volume of 65-75 decibels and at a frequency of 1000 Hz (Webb et al, 2015); (Nocker-Ribaupierre et al, 2015); and (Jabraeili et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…stabilization of respiratory rate) in premature infants [41][42][43] and on the preterm brain development [44]. Until recently, only a few randomized controlled trials have reported data for parents, despite the fact that the integration of parents is described in family-centered music therapy approaches [45][46][47]. The focus of the above mentioned studies has been limited to reducing maternal anxiety [45,[48][49][50][51][52], the reduction of stress [53], the improvement of the mother-infant interaction [54,55] and bonding [45,47,49].…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, only a few randomized controlled trials have reported data for parents, despite the fact that the integration of parents is described in family-centered music therapy approaches [ 45 47 ]. The focus of the above mentioned studies has been limited to reducing maternal anxiety [ 45 , 48 52 ], the reduction of stress [ 53 ], the improvement of the mother-infant interaction [ 54 , 55 ] and bonding [ 45 , 47 , 49 ]. Until now, studies on whether a reduction in the symptoms of postpartum depression in mothers of premature infants can be achieved using music therapy [ 56 , 57 ] are rare.…”
Section: Introductionmentioning
confidence: 99%